STRATEGY FOR DEVELOPMENT OF HUMAN RESOURCE CAPACITY IN CAPITALIZING TOURISM POTENTIALS (Study on Watu Hadang Tourism Village, Umalulu District, East Sumba Regency) - Alas Satya Samuel Buditomo; Hamidah Nayati Utami; Arik Prasetya (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
This study aims to determine the strategy for developing the capacity of human resources in Watu Hadang Village, East Sumba Regency, Umalulu District to be able to optimally utilize the tourism potential in the village. The research method used is descriptive qualitative method. The findings indicated that there are six strategies to enhance the human resources capacity in Watu Hadang Village, Umalulu District, East Sumba Regency. Firstly, engaging the local human resources in training programs and capacity building initiatives as key players in the tourism sector. Secondly, providing a variety of essential training programs for individuals involved in the tourism industry to foster its growth in Watu Hadang Village, including professional certification, hospitality and homestay management, technology utilization for marketing, product enhancement, leadership training, creative entrepreneurship, and more. Thirdly, making use of financial aid from both governmental and non-governmental sources to support the development of tourism in Watu Hadang Village. Fourthly, allocating village funds to address the educational needs of the community by acquiring school buses. Fifth, utilizing village funds for educational scholarships to enable local residents to pursue education up to the senior high school level. Sixth, Collaborating with stakeholders like the village government, tourism office, NGOs, and other relevant parties can enhance current village institutions.